The Influence of Situational Leadership Style on Teacher Performance (Case Study at Smk Cahaya Surya) - Puspitaningrum, Yuliawati; Syahidin, Aris; Santyo, Debby (CV. Publikasi Indonesia, 2025)
Teacher performance is pivotal in education quality, yet challenges like unsupportive work environments and inconsistent leadership persist at SMK Cahaya Surya Kediri. Prior studies emphasize leadership’s role but lack focus on situational adaptability in vocational schools. This study analyzes the influence of situational leadership style on teacher performance, addressing gaps in context-specific leadership effectiveness. A quantitative approach was employed with 80 teachers sampled via convenience sampling. Data were collected through questionnaires and analyzed using Likert scales, validity/reliability tests, and multiple linear regression. Situational leadership significantly enhances teacher performance (beta = 39.4%, *p* < 0.05), with participatory behaviors (mean = 4.02) being most effective. The work environment’s moderating role was identified as a secondary factor. Principals should adopt adaptive leadership strategies to optimize teacher performance. Future research could explore longitudinal effects or integrate transformational leadership for broader applicability.